Transcriptome analysis insight into ethylene metabolism and pectinase activity of apricot (Prunus armeniaca L.) development and ripening - Min Xu (Nature Portfolio, 2021)
Abstract Ethylene metabolism is very important for climacteric fruit, and apricots are typical climacteric fruit. The activity of pectinase is closely related to fruit firmness, which further affects fruit quality. To better understand ethylene metabolism, pectinase activity and their molecular regulation mechanisms during the development and ripening of apricot fruit, ethylene metabolism, pectinase activity and the “Luntaibaixing” apricot fruit transcriptome were analyzed at different developmental stages. Ethylene metabolic precursors, enzyme activities and ethylene release increased during fruit development and ripening, with significant differences between the ripening stage and other stages (P < 0.05). Fruit firmness decreased significantly from the S1 to S5 stages, and polygalacturonase, pectin methylesterase, and pectin lyase activities were significantly higher in the S5 stage than in other stages. RNA sequencing (RNA-seq) analysis of fruit resulted in the identification of 22,337 unigenes and 6629 differentially expressed genes (DEGs) during development and ripening, of which 20,989 unigenes are annotated in public protein databases. In functional enrichment analysis, DEGs among the three stages were found to be involved in plant hormone signal transduction. Four key genes affecting ethylene metabolism, six key ethylene signal transduction genes and seven genes related to pectinase in apricot fruit were identified by KEGG pathway analysis. By RNA-sequencing, we not only clarified the molecular mechanism of ethylene metabolism during the ripening of "Luntaibaixing" apricot fruit but also provided a theoretical basis for understanding pectin metabolism in apricot fruit.